2011
DOI: 10.1007/s00228-011-1134-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of drug metabolizing enzyme genotype to plasma levels as well as myelotoxicity of cyclophosphamide in breast cancer patients

Abstract: The myelotoxicity in patients receiving FAC is related to the activity of the phase-II enzyme GSTA1 but is independent of the formation of 4-OH-CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…[20][21][22] Phosphoramide alkylates the guanine base of DNA at the N7 position of the imidazole ring and hence triggers apoptosis due to the formation of guanine-adenine intrastrand cross-links. 23 Cy is converted to 4-OH-Cy in the liver, predominantly by CYP2B6 (Ekhart et al, 24 Raccor et al 25 and Cho et al 26 ) and to a lesser extent by CYP3A4, CYP3A5, CYP2C9 and CYP2C19 (Afsar et al 27 and Fernandes et al 28 ). High inter-and intra-individual variability in Cy kinetics has been reported, which affects treatment efficacy and toxicity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[20][21][22] Phosphoramide alkylates the guanine base of DNA at the N7 position of the imidazole ring and hence triggers apoptosis due to the formation of guanine-adenine intrastrand cross-links. 23 Cy is converted to 4-OH-Cy in the liver, predominantly by CYP2B6 (Ekhart et al, 24 Raccor et al 25 and Cho et al 26 ) and to a lesser extent by CYP3A4, CYP3A5, CYP2C9 and CYP2C19 (Afsar et al 27 and Fernandes et al 28 ). High inter-and intra-individual variability in Cy kinetics has been reported, which affects treatment efficacy and toxicity.…”
Section: Introductionmentioning
confidence: 98%
“…32 However, recent studies have concluded that CYPs polymorphisms does not have a significant role in the response variation to Cy. 25,27,28 In the present study, we investigated the expression of CYP2J2 as well as several other CYPs in 20 patients undergoing stem cell transplantation and treated with Cy compared with 12 healthy volunteers. We also investigated the role of CYP2J2 in Cy bioactivation in vitro using leukemic cell lines as well as complementary DNA-expressed CYP2J2 microsomes.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that both CYP2B6 and CYP2C19 are important in the biotransformation and activation of this prodrug in vitro (Chang et al, 1993(Chang et al, , 1997Huang et al, 2000;Griskevicius et al, 2003;Xie et al, 2003;Chen et al, 2004) and in vivo (Timm et al, 2005;Xie et al, 2006;Nakajima et al, 2007;Helsby et al, 2010;Afsar et al, 2011). However, whereas there is some evidence to support altered therapeutic response and/or toxicity in patients who have single nucleotide polymorphisms (SNP) variants of either of these P450 enzymes (Takada et al, 2004;Elmaagacli et al, 2007;Singh et al, 2007;Tran et al, 2008;Bray et al, 2010;Melanson et al, 2010;Afsar et al, 2011;Black et al, 2012), not all studies confirm this effect (Petros et al, 2005;Ekhart et al, 2008;Low et al, 2009;Yao et al, 2010;Winoto et al, 2011). This lack of consistency in the published literature may in part relate to invalid assumptions regarding the functional changes associated with each CYP2B6 genotype and hence misclassification of metabolizer categories.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, these same CYP2B6 genotypes were grouped together as "variant," irrespective of whether individual genotypes led to increased or decreased function (Gor et al, 2010;Afsar et al, 2011). Such errors can lead to invalid analysis of the data, which emphasizes the importance of the correct assignment of CYP2B6 genetic variants with respect to cyclophosphamide metabolizer status (Helsby and Tingle, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation